IMPROVING STUDENTS' READING COMPREHENSION THROUGH THE DRTA STRATEGY - Muchsin Muchsin (UNIVERSITAS SERAMBI MEKKAH, 2023)
This research is aimed at improving the reading comprehension ability of Serambi Mekkah English students on narrative texts through DRTA (directed reading thinking activity). The strategy was conducted beyond the consideration of finding that the researcher found during the preliminary study. Many of the students at the university, especially the students of English department encountered problems in comprehending the texts or passages. It was found that students hardly understood the narrative text especially about factual detail, main idea, and word meaning. Therefore, researchers implemented the DRTA strategy. The researcher used collaborative classroom action research design. It was conducted in two cycles by following the procedures of action research, i.e., planning, implementing, observing, and reflecting. Each cycle was carried out two meetings of strategy implementation and one meeting for the test. The data of the study was gathered through observation sheet, students' observation sheet, reading comprehension test and questionnaire. The result of the research showed that the DRTA strategy has improved students reading comprehension. The improvement could be seen from the increase of the students' score in reading comprehension which reached the target score (70 in the range of 0 to 100), i.e., in preliminary the mean score was 6,42. Then the mean score increased to 6,96 in post-test cycle I. The mean score of the students proficiency improved to 8,33 in post-test cycle II. This evidence suggested that the students had already reached the intended target score, namely 7,00. It means that many students responded that the application of DRTA strategy was helpful to improve their reading skill, and the strategy was very good to improve the student's comprehension of main idea, factual detail and word meaning.